Our future together industry perspectives: Future of professional learning and entrepreneurship - SEOW, Poh Sun (Institutional Knowledge at Singapore Management University, 2017)
This report 2017 marks the second collaboration between ISCA and ICAEW after the successful launch of “Our Future Together” report in 2016 to inspire professional accountants to critically think about what the future holds for Singapore and the accountancy profession. How should accountants embrace transformation in the digital age? How should learning be redefined for the accountancy profession? How can organisational culture encourage innovation and an enterprising spirit in accountants? This report aims to shape the discussion on how education, training and professional learning should be redefined to develop professional accountants who are future-ready, so that they can continue to look forward to a bright future in the new economy that is well underway.